2011
DOI: 10.4161/rna.8.5.16151
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro analysis of 6S RNA-templated short transcripts inBacillus subtilis

Abstract: (2011) In vivo and in vitro analysis of 6S RNA-templated short transcripts in Bacillussubtilis, RNA Biology, 8:5,[839][840][841][842][843][844][845][846][847][848][849]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
123
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(133 citation statements)
references
References 18 publications
10
123
0
Order By: Relevance
“…The RNA was observed to reach highest steadystate levels between early and mid-exponential phase and to decrease toward stationary phase Barrick et al 2005;Beckmann et al 2011). Deviating from these observations, B. subtilis 6S-2 RNA levels were also reported to remain fairly constant in exponential and stationary phase (Trotochaud and Wassarman 2005;Cavanagh et al 2012).…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…The RNA was observed to reach highest steadystate levels between early and mid-exponential phase and to decrease toward stationary phase Barrick et al 2005;Beckmann et al 2011). Deviating from these observations, B. subtilis 6S-2 RNA levels were also reported to remain fairly constant in exponential and stationary phase (Trotochaud and Wassarman 2005;Cavanagh et al 2012).…”
Section: Introductionmentioning
confidence: 68%
“…We have demonstrated in vitro that the σ A -RNAP holoenzyme is able to synthesize pRNAs on 6S-2 RNA as a template (Beckmann et al 2011). So far, deep sequencing analyses have not provided evidence for the synthesis of 6S-2 RNA-derived pRNAs in vivo (Irnov et al 2010;Beckmann et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of heparin, pRNA sizes increase (Supplemental Fig. S2) but appear to have limited in vivo significance; as pRNAs of length z10-14 nt are known to be produced within 15-30 sec of rapid outgrowth in E. coli (Wurm et al 2010) and are very similar in size to the pRNAs observed in H. pylori (12 nt long) ) and B. subtilis (8-12 nt long) (Beckmann et al 2011). Longer RNAs complementary to a pRNA probe have been detected by Northern blot from E. coli, but they start to accumulate only after 1-2 min of outgrowth (Wurm et al 2010).…”
Section: S:prna:e Release Intermediate Found Between Bound (S2) and mentioning
confidence: 99%